Critiquing the motivations for Luther’s reformation (2018)
What informed the engagement of this topic is the mixed feelings or misrepresentations that some Christians express about Martin Luther, the Chief Pioneer or Prince of what we call Protestantism. While it is an established fact in a section of Christianity that Luther was a political reformer, others see him as a religious reformer. Such divergent opinions are capable of distorting historical facts and have the tendency of promoting erroneous ideas about the ideal that Luther stood for. Therefore, the concern of this paper is to investigate the socioeconomic, political and religious contexts which spurred reactions by some intellectual church men that eventually culminated in the 16th century reformation. This attempt becomes imperative in order to have a clearer picture of the situations before the reformation and to assess the strategies adopted by the reformers, especially Martin Luther in order to determining the veracity of the claim that Luther's reformation was politically motivated.